2021
DOI: 10.20473/ijar.v3i12021.17-21
|View full text |Cite
|
Sign up to set email alerts
|

Opioid-Sparring and Multimodal Analgesia as Parts of Enhanced Recovery After Surgery (ERAS) Applied In The Ksatria Airlangga Floating Hospital

Abstract: Introduction: Enhanced Recovery After Surgery (ERAS) protocol is a perioperative multimodal service program designed to achieve a faster surgical recovery period and a better outcome, the key in reducing morbidity in surgery is by reducing the “surgical injury” and reducing the body’s stress response caused by the surgery. The success of the ERAS protocol depends on the interpretation and collaboration of the multidisciplinary team, therefore though the protocol is carried out in a hospital that has sufficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…ERAS has been proven to be well implemented in social-based health services such as the Airlangga Ksatria Floating Hospital. 10 When properly prepared, ERAS is not only able to shorten the length of stay in the hospital but also minimize the incidence of postoperative complications. 3,13 several other studies have found that adherence to the ERAS protocol is associated with lower postoperative complications in liver cancer patients undergoing liver resection surgery.…”
Section: Discussionmentioning
confidence: 99%
“…ERAS has been proven to be well implemented in social-based health services such as the Airlangga Ksatria Floating Hospital. 10 When properly prepared, ERAS is not only able to shorten the length of stay in the hospital but also minimize the incidence of postoperative complications. 3,13 several other studies have found that adherence to the ERAS protocol is associated with lower postoperative complications in liver cancer patients undergoing liver resection surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Local anesthetics also act on autonomic nerves, causing vasodilation of peripheral blood vessels through sympathetic blockage in the posterior hypothalamus [ 18 ]. When combined with enhanced recovery after surgery protocols, regional anesthesia can decrease the need for opioids, thereby reducing opioid-related side effects such as sedation, nausea, vomiting, urinary retention, respiratory depression, bowel dysfunction, ileus, and sleep disturbances [ 19 ].…”
Section: Introductionmentioning
confidence: 99%